2015
DOI: 10.1142/s1793292015500253
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Injection Using Carbon Nanotube: A Molecular Dynamics Study

Abstract: Determination of an injection condition which is minimally invasive to the cell membrane is of great importance in drug and gene delivery. For this purpose, a series of molecular dynamics (MD) simulations are conducted to study the penetration of a carbon nanotube (CNT) into a pure POPC cell membrane under various injection velocities, CNT tilt angles and chirality parameters. The simulations are nonequilibrium and all-atom. The force and stress exerted on the nanotube, deformation of the lipid bilayer, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, the reported penetration forces in these studies do not align appropriately with experimental data [8]. For instance, Mahbobi et al [5] reported that the penetration force for a Carbon Nanotube (CNT) with a diameter of 1.53 nm is approximately 4.6 nN. However, Penedo's experimental findings suggest that the force for a 50 nm diameter is around 0.1 nN.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the reported penetration forces in these studies do not align appropriately with experimental data [8]. For instance, Mahbobi et al [5] reported that the penetration force for a Carbon Nanotube (CNT) with a diameter of 1.53 nm is approximately 4.6 nN. However, Penedo's experimental findings suggest that the force for a 50 nm diameter is around 0.1 nN.…”
Section: Introductionmentioning
confidence: 84%
“…Previous research has focused on investigating the mechanical aspects of MDT, specifically the forces and initial velocities necessary for penetrating tissues and cells. For instance, Mahboobi et al [5] conducted Molecular Dynamics(MD)-based simulations to investigate penetration force as a function of impact angle, as well as to examine projectile buckling. Similarly, Raczynski et al [6] obtained force-indentation length diagrams through MD simulations, investigating different constant indentation velocities.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, this study figured out the effects of the size and type of CNT on the mechanism of spontaneous exothermic insertion of CNTs into the lipid bilayer membranes. MD simulations have been employed to examine the penetration of a CNT into a pure 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) cell membrane under various injection velocities, CNT tilt angles and chirality parameters [ 24 ]. Raczyński et al [ 25 ] demonstrated a series of steered molecular dynamics (SMD) simulations on two types of armchair CNTs, open-ended and capped, to examine the process of nanoindentation of the phospholipid bilayer by SWCNTs.…”
Section: Introductionmentioning
confidence: 99%